Beyond Vibranium: Revealing Power Dynamics in Black Panther: ‘Wakanda Forever’ Movie (2022) - Jacobus, Benaiya Tristan; Manullang, Petronio Pirdon; Setiawan, Steven Febryan; Tan, Emmanuel; Noah, Abimanyu; Maukary, Brandon Ezra (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2024)
This study aims to show how power operates through knowledge and control, which plays out in the movie